2013
DOI: 10.1074/jbc.m113.512806
|View full text |Cite
|
Sign up to set email alerts
|

Body Fluid Exosomes Promote Secretion of Inflammatory Cytokines in Monocytic Cells via Toll-like Receptor Signaling

Abstract: Background: Exosomes, secreted from cells, have immunomodulatory capacities. Results: NFB-and STAT3-mediated cytokine release is triggered by various types of ex vivo exosomes in a TLR-dependent fashion. Conclusion: Exosomes have inherent signaling capacities important for global inflammatory responses.Significance: Detailed knowledge about intercellular communication in cancer and inflammatory diseases is crucial for development of new therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
179
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(192 citation statements)
references
References 45 publications
(36 reference statements)
7
179
2
1
Order By: Relevance
“…However, mild activation is known to be protective (Mathur et al 2011. Other studies have suggested a link between body fluid exosomes and TLR-dependent signaling pathways, possibly mediating immunosuppressive and anti-inflammatory pathways (Bretz et al 2013, Zhang et al 2014.…”
Section: Evs As a Potential Therapy For Cardiometabolic Diseasementioning
confidence: 99%
“…However, mild activation is known to be protective (Mathur et al 2011. Other studies have suggested a link between body fluid exosomes and TLR-dependent signaling pathways, possibly mediating immunosuppressive and anti-inflammatory pathways (Bretz et al 2013, Zhang et al 2014.…”
Section: Evs As a Potential Therapy For Cardiometabolic Diseasementioning
confidence: 99%
“…Clayton and colleagues reported that TEX selectively impaired human lymphocyte responses to IL-2 (48). TEX-delivered signals trigger the activation of NF-κB and STAT3 (51) and alter cytokine profiles in T cells, reprogramming them toward the Th2 phenotype (51). TEX signal to monocytes, inducing secretion of the proinflammatory cytokines IL-6, TNF-α, IL-1β, and granulocyte-CSF (G-CSF) (52).…”
Section: Functional Attributes Of Texmentioning
confidence: 99%
“…The delayed activation of STAT-3 in vascular smooth muscle cells and in response to tumor-derived exosomes in THP-1 cells has been reported (48,57). In this study, exosomal blockade in hypertrophied cardiomyocytes had no effect on STAT-3 phosphorylation in myocyte-conditioned fibroblasts at earlier time points; however, it dampened STAT-3 activity at later phases.…”
Section: Fig 11mentioning
confidence: 37%
“…Besides occurring in a secreted form, IL-6 may also reside in cell-derived exosomes, as suggested earlier (48). Myocyte-derived exosomes have not yet been characterized during AngII-mediated hypertrophy.…”
Section: Fig 11mentioning
confidence: 86%